Kidney failure as an unusual initial presentation of biclonal gammopathy (IgD multiple myeloma associated with light chain disease) – A case report - Rabrenović, Violeta; Mijušković, Zoran; Marjanović, Slobodan; Rabrenović, Milorad; Jovanović, Dragan; Antić, Svetlana; Ignjatović, Ljiljana; Petrović, Milica; Pilčević, Dejan (Vojnosanitetski pregled, 2015)
Introduction. Immunoglobulin D (IgD) myeloma is a rare disease, about 2% of all myelomas, even rarer when accompanied with another multiple myeloma in biclonal gammopathy. We presented a case of biclonal gammopathy – associated manifestation of IgD myeloma and light chain disease in a patient who initially had renal failure. Case report. 37-year-old male approximately one month before hospitalization began to feel malaise and fatigue along with decreased urination. Laboratory analysis revealed azotemia. A dialysis catheter was placed and hemodialysis started. The patient was then admitted to our hospital for further tests and during admission, objective examination revealed pronounced paleness with hepatosplenomegaly and hypertension (170/95 mmHg). Laboratory analysis showed erythrocyte sedimentation rate 122 mm/h, expressed anemic syndrome (Hb 71 g/L) and renal failure dialysis rank: creatinine 1,408 μmol/L, urea31.7 mmol/L. There was two M components in serum protein electrophoresis: IgD lambda and free light chain lambda. Proteinuria was nephrotic rank (5.4 g/24 h), whose electrophoresis revealed 2 M components – massive in α 2 fraction of 71%; 7% in the discrete β fraction, beta 2M /serum 110 mg / L, in urine 1.8 mg/L – extremely high; IgL kappa / lambda index 1 : 13 (reference value ratio 2 : 1). The findings pointed to double myeloma disease: IgD myeloma and Bence Jones lambda myeloma. Bone biopsy confirmed IgD myeloma lambda 100% infiltration medulla predominantly plasmablasts. The treatment continued with hemodialysis 3 times per week with chemotherapy protocol bortezomib, doxorubicin, dexamethasone. After 4 cycles of chemotherapy, there was a decrease of IgD, λ – light chains, reduction in proteinuria (1.03 g/24 h), so hemodialysis was reduced to once per week. Six months after treatment initiation the patient underwent autologous bone marrow transplantation. In a 2-year follow-up period double myeloma disease showed complete remission. Conclusion. The presented rare form of double myeloma disease with initial renal insufficiency underscores the importance of careful observation and teamwork that can alter the course of this serious disease.